The Impact of Cardiac Injury on COVID-19 Patients Mortality: A Systematic Review and Meta-Analysis - Nisa Amnifolia Niazta; Hiradipta Ardining; Muchammad Dzikrul haq Karimullah (Universitas Brawijaya, 2020)
Background: Cardiovascular system was the second most common organ system affected by COVID-19. Cardiac injury has been reported in many COVID-19 cases. The purpose of this study was to investigate the correlation between cardiac injury with mortality in COVID-19 patients.Methods: We performed a systematic review and meta-analysis study. The relevant studies were identified through scientific electronic databases such as PubMed, Cochrane, and ScienceDirect up to August 2020. The study quality assessment was conducted using the GRADE approach. The pooled odds ratio (OR) and 95% confidence interval (CI) were estimated using the random-effects model. Results: A total of 10 studies involving 2619 patients were included in the meta-analysis. The incidence of cardiac injury in COVID-19 patients was 28.5%. The all-cause mortality was significantly higher in patients with cardiac injury (52.8% vs. 13.1%; OR = 13.78; 95% CI = 7.22-26.32; I 2 = 88%; Z= 7.95; P < 0.00001).Conclusion: Cardiac injury is associated with higher mortality in COVID-19 patients. The cardiac injury should be considered as an important variable in the risk stratification for mortality in COVID-19.